TRENDS IN INDUSTRY CONSOLIDATION PROCESSES AND STRUCTURAL CHANGES IN THE AUTOMOTIVE INDUSTRY OF THE RUSSIAN FEDERATION - S. Vasilenko (Вестник университета)
The situation in the Russian automotive industry in the past few years can be characterized as a high degree of uncertainty. Since the global economic crisis began, the automotive industry of the Russian Federation has been one of the most «affected» industries. The article deals with the dynamics the automotive industry development of the rate in the Russian Federation from 2011 to 2015. According to analysis results, the degree of the automotive industry concentration was evaluated, as well as the stage of industry consolidation was determined in 2015 respectively. The author believes that the structural changes in the automotive industry are encouraging TOP-management to seek strategic solutions in order to achieve competitive advantages in the industry.